(untitled) (International Journal of Health, Animal Science and Food Safety, 2015)
The aim of this study was to evaluate the in vitro relative bioefficacy of RRR-α-tocopherol (RRR- α-T) versus all-rac-α-tocopherol (all-rac-α-T) in counteracting the cytotoxic effect induced by H2O2 in Bovine Mammary Epithelium – University of Vermont (BME-UV1) and Madin-Darby Canine Kidney (MDCK) cells. The range of RRR- α-T and all-rac- α-T concentrations selected for the oxidative challenge experiments was 100µM - 1nM. To study the bioefficacy of RRR- α-T and all-rac- α-T, MTT and LDH tests were performed. Cells were pre-incubated for 3 h with selected a-tocopherol concentrations and then exposed to increasing H2O2 concentrations ranging from 125 to 750µM for the following 24h. Concerning the cell viability, the pre-treatments with 100µM of RRR- α-T and 100µM all-rac-α-T were able to significantly (P<0.05) counteract the effect induced by 750 µM of H2O2 in BME-UV1. In MDCK the pre-treatment with 1nM of all-rac-α-T was able to significantly (P<0.05) reduce the effect of 125 and 150 mM H2O2. In MDCK cells, the pre-incubation with all-rac-α-T determines a significant reduction of the membrane damage, induced by 175 µM of H2O2. In conclusion, RRR-α-T and all-rac-α-T have shown the ability to counteract the oxidative effects of H2O2, however further investigation will help to better understand their specific mechanism of action in vitro.